1994
DOI: 10.1093/clinchem/40.7.1327
|View full text |Cite
|
Sign up to set email alerts
|

Stability of plasma lactate in vitro in the presence of antiglycolytic agents

Abstract: The use of plasma lactate to assess metabolic or circulatory impairment requires definition of critical preanalytical and analytical parameters. Stability has been documented for only 15 min after acquisition when samples were collected with fluoride and transported on ice. We examined time elapsed before analysis, storage temperature, and the antiglycolytic agent used to define preanalytical conditions. Plasma lactate was measured with a Kodak Ektachem 700XR analyzer. In controlled studies on volunteers, stor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
1
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 0 publications
4
31
1
2
Order By: Relevance
“…35 Whether this phenomenon occurs in hyperlactatemia unrelated to exercise is unclear, but it would be expected to affect both measurement techniques similarly unless there was a significant time lag between sample analyses. Leukocytosis also has been suggested to falsely increase blood lactate concentration, 36 but this is unlikely to have been a factor in this study because most horses had normal white blood cell counts on presentation.…”
Section: Discussionmentioning
confidence: 73%
“…35 Whether this phenomenon occurs in hyperlactatemia unrelated to exercise is unclear, but it would be expected to affect both measurement techniques similarly unless there was a significant time lag between sample analyses. Leukocytosis also has been suggested to falsely increase blood lactate concentration, 36 but this is unlikely to have been a factor in this study because most horses had normal white blood cell counts on presentation.…”
Section: Discussionmentioning
confidence: 73%
“…1 Sodium fluoride inhibits several glycolytic enzymes and preventing significant increases in [LAC]. 25,26 Although, only a small number of samples were used for the pilot study in this report, several investigations have reported the stability of [LAC] when blood samples are collected into sodium fluoride and refrigerated. 25,26 The optimal frequency of [LAC] measurement or duration of [LAC] measurement in equine patients remains to be determined; in human reports, [LAC] is measured every 6-24 hours (and occasionally more frequently) for the 1st 3-5 days after hospital admission.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Although, only a small number of samples were used for the pilot study in this report, several investigations have reported the stability of [LAC] when blood samples are collected into sodium fluoride and refrigerated. 25,26 The optimal frequency of [LAC] measurement or duration of [LAC] measurement in equine patients remains to be determined; in human reports, [LAC] is measured every 6-24 hours (and occasionally more frequently) for the 1st 3-5 days after hospital admission. Despite these limitations serial measurement of [LAC] appears to have prognostic value in the management of critically ill adult horses and warrants additional investigations in larger prospective studies targeting specific diagnostic groups.…”
Section: Discussionmentioning
confidence: 99%
“…349 At room temperature, lactate concentrations in heparinized whole blood will increase by 0.2-0.5 mmol/L (1.8-4.5 mg/dL) per 30 minutes, 137,350,351 but should only rise by 0.2 mmol/L (1.8 mg/dL) after 120 minutes if stored in an ice bath. 351,352 Serum lactate concentrations will also significantly increase in the time required for blood to clot in a serum collection tube. 137 Collection tubes with sodium fluoride, a glycolytic inhibitor, and potassium oxalate, an anticoagulant, are preferred for samples from dogs and cats being sent to an external lab.…”
Section: Collection Tubesmentioning
confidence: 99%
“…137 Collection tubes with sodium fluoride, a glycolytic inhibitor, and potassium oxalate, an anticoagulant, are preferred for samples from dogs and cats being sent to an external lab. 137,351 The anticoagulant sodium citrate interferes with lactate measurement and therefore should be avoided. 353,354 These are, however, general recommen-dations and sample processing should be based on recommendations for the specific analyzer or reference laboratory.…”
Section: Collection Tubesmentioning
confidence: 99%